Populism in Trump’s China Trade Policy: An Analysis Focused on the “America First” Narrative - Jiang, Mingyan (Transactions on Economics, Business and Management Research, 2024)
This analysis investigates populism in Donald Trump’s China trade policy through the lens of his “America First” mantra. It initiates with defining populism and its manifestation in Trump’s rhetoric. The “America First” agenda, with its historical roots recontextualized, embodies economic protectionism, anti-globalism, anti-immigration, and a preference for non-interference in international conflicts. Trump’s discourse frames globalization and unfair trade practices, particularly those attributed to China, as threats to American prosperity and security. The study dissects how this narrative was operationalized to justify aggressive trade actions, including tariffs and efforts to revise trade agreements, aiming to reclaim control over the U.S. economy amidst perceived imbalances. The study then scrutinizes the populist execution of this policy, focusing on trade war, technology competition, and economic decoupling. Its implications on China, the US, and their relations are assessed, identifying the impacts on China’s export sector, technological development, and global diplomatic efforts. Conversely, it discusses the repercussions for the U.S. economy, particularly in agriculture and manufacturing, and the broader effects on international trade relations and the global economic order. The conclusion underscores the multifaced consequences of the “America First” policy, emphasizing the need for diplomatic engagement, strategic recalibration, and a reevaluation of populism’s role in international economic relations.